Attribute‐based credentials with cryptographic collusion prevention. Issue 18 (7th July 2015) - Hajny, Jan; Dzurenda, Petr; Malina, Lukas
Abstract: Cryptographic attribute‐based credentials (ABCs) allow users to prove their personal attributes remotely and in a privacy‐friendly way. While staying anonymous and untraceable, the users are able to prove their attributes, such as age, membership, or nationality, before using a network service. Unfortunately, there are very few practical cryptographic ABC schemes available today. Furthermore, some existing schemes rely on the hardware tamper‐resistance of smart cards to avoid collusion attacks. The trust in hardware limits the usage of such schemes on poorly protected cards and on smart phones. In this paper, we present the full cryptographic specification of an ABC scheme, which makes the collusion attacks impossible even on insecure hardware like mobile phones. Furthermore, the scheme provides features, which are difficult to achieve using existing schemes, namely the practical revocation of users, the de‐anonymization of malicious users, and the unlinkability of verification sessions. Besides the cryptographic architecture, we also present our practical implementation on a smart phone and embedded platforms. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : n this paper, we present the full crytographic specification of an attribute‐based credential scheme that makes the collusion attacks impossible even on insecure hardware like mobile phones. Furthermore, the scheme provides features, which are difficult to achieve using existing schemes, namely the practical revocation of users, the de‐anonymization of malicious users, and the unlinkability of verification sessions.